2007
DOI: 10.1080/18811248.2007.9711298
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Experiments of Electrometallurgical Pyroprocessing Using Plutonium Oxide

Abstract: ÃÃElectrometallurgical pyroprocessing is a promising technology to realize actinide fuel cycle. Integrated experiments to demonstrate electrometallurgical pyroprocessing of PuO 2 in continuous operation were carried out. In each test, 10-20 g of PuO 2 was reacted with Li reductant to form metal product. The reduction products were charged in an anode basket of the electrorefiner with LiCl-KCl-UCl 3 electrolyte. Using the anode, deposition of uranium on the solid cathode was carried out when PuCl 3 /UCl 3 conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…CRIEPI has been studying these processes since 1985, and has carried out joint studies with groups including Argonne National Laboratory, European Commission Joint Research Centre -The Institute for Transuranium elements, and Japan Atomic Energy Agency. The feasibility of pyrometallurgical reprocessing has been demonstrated through many laboratory-scale experiments (5)- (7) . The development of the engineering technology required for pyrometallurgical reprocessing is a key issue for its industrial realization.…”
Section: Introductionmentioning
confidence: 99%
“…CRIEPI has been studying these processes since 1985, and has carried out joint studies with groups including Argonne National Laboratory, European Commission Joint Research Centre -The Institute for Transuranium elements, and Japan Atomic Energy Agency. The feasibility of pyrometallurgical reprocessing has been demonstrated through many laboratory-scale experiments (5)- (7) . The development of the engineering technology required for pyrometallurgical reprocessing is a key issue for its industrial realization.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] During pyroprocessing, amounts of waste salts (LiCl-KCl eutectic, NaCl-KCl eutectic or LiCl melts) containing chlorides of TRU and FPs (e.g., alkali, alkaline-earth, and rareearth FPs) are generated. 4,5) These fission products are highly radioactive.…”
Section: Introductionmentioning
confidence: 99%
“…Similar problems regarding undesirable salt vapor depositions onto various system components, such as the crucible assembly and salt vapor transport tube between the vaporizing crucible and collecting crucibles, and the problems of equipment maintenance due to the migration of undesirably deposited salt were reported in the other previous salt distillation studies. 8,9) A new salt distillation system, a closed-chamber distillation system, is developed to substantially enhance the recovery efficiency of vaporized salt. This study describes the principle of the design and operation and the results of test operations of the lab-scale closed chamber salt distillation system.…”
Section: Introductionmentioning
confidence: 99%
“…Some problems such clogging and corrosion of system components due to the loss of corrosive salt were reported in the previous salt distillation studies. [7][8][9] Salt distillation test systems typically consist of a distiller, a vapor transport pipe, a condenser, a filter, and a vacuum controlling unit. Our previous fundamental salt distillation study also showed that this kind of distillation system had difficulty in the recovery of distilled salt.…”
Section: Introductionmentioning
confidence: 99%